2002
DOI: 10.1093/toxsci/70.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pulmonary Responses of Three Laboratory Rodent Species to Subchronic Inhalation of Pigmentary Titanium Dioxide Particles

Abstract: Female mice, rats, and hamsters were exposed to 10, 50, or 250 mg/m(3) pigmentary titanium dioxide (p-TiO(2)) particles for 6 h per day and 5 days per week for 13 weeks with recovery groups held for an additional 4, 13, 26, or 52 weeks postexposure (46 weeks for the p-TiO(2)-exposed hamsters). At each time point p-TiO(2) burdens in the lung and lymph nodes and selected lung responses were examined. The responses studied were chosen to assess a variety of pulmonary parameters, including inflammation, cytotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
138
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(151 citation statements)
references
References 15 publications
9
138
1
3
Order By: Relevance
“…A research program to investigate inter-species differences as a result of exposure to TiO 2 and to conduct detailed epidemiological surveys of the major manufacturing sites was initiated by a consortium of TiO 2 manufacturers in Europe (under the European Chemistry Industry Council; CEFIC) and North America (under the American Chemistry Council; ACC). Some detailed results published from these studies showed distinct species differences in lung responses, particle distributions and clearance rates (Bermudez et al, 2002(Bermudez et al, , 2004.…”
Section: Introductionmentioning
confidence: 97%
“…A research program to investigate inter-species differences as a result of exposure to TiO 2 and to conduct detailed epidemiological surveys of the major manufacturing sites was initiated by a consortium of TiO 2 manufacturers in Europe (under the European Chemistry Industry Council; CEFIC) and North America (under the American Chemistry Council; ACC). Some detailed results published from these studies showed distinct species differences in lung responses, particle distributions and clearance rates (Bermudez et al, 2002(Bermudez et al, , 2004.…”
Section: Introductionmentioning
confidence: 97%
“…TNP toxicity has been observed in diverse models, such as rodents [15][16][17][18], aquatic organisms [19][20][21], and human cells [22][23][24]. Female workers were reported to experience shortness of breath and pleural effusions after 5-13 months of exposure in a polyacrylic ester nanoparticle processing factory [25], raising significant doubt about the human safety of TNPs.…”
Section: Introductionmentioning
confidence: 99%
“…If the doses were expressed as surface area rather than mass in the experiment, the fact that the doseresponse relationship appeared as a straight line, led to the opinion that larger surface area is a factor in the strong inflammatory response to TiO 2 nanoparticles 7,27,30) . Bermudez et al 31,32) compared the results of a 13-week inhalation study of TiO 2 nanoparticles in rat, hamster and mouse with previous reports of TiO 2 microparticles. They reported, that at the same mass-based exposures, greater pulmonary inflammatory responses were seen in the groups exposed to TiO 2 nanoparticles than in the groups exposed to TiO 2 microparticles, and concluded that differences in surface area were the cause of this result.…”
Section: Tio 2 Nanoparticlesmentioning
confidence: 99%
“…One of the possible reasons for disagreement is that many studies have been performed using particles with different particle size, surface properties, impurities and crystal structures, involving complex interactions among many factors, and it has been difficult to separate the sole effects of particle size and surface area among many factors. For example, in the research of Bermudez et al 31,32) and Sager et al 35) the TiO 2 nano-and micro-particles used came from different sources and had different crystal structures. Both used the 80% anatase -20% rutile form of TiO 2 particles, generally known by the product name P25, made by Evonik as TiO 2 nanoparticles.…”
Section: Tio 2 Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation